Localised optical states in a structure formed by two oppositely handed cholesteric liquid crystal layers and a metal. Issue 4 (16th March 2017) - Pyatnov, Maxim V.; Vetrov, Stepan Ya.; Timofeev, Ivan V.
ABSTRACT: A new model for observing localised optical states in a structure containing a cholesteric liquid crystal is proposed. The dependence of the mode frequency on the angle between directors at the interface of oppositely handed cholesterics is established. The effect of the metal layer thickness on localisation of light at the localised state frequency is studied. Polarisation features of the transmission spectrum are investigated. The possibility of experimental implementation of the proposed structure is discussed. GRAPHICAL ABSTRACT: